Professional Formation in Spain and Germany - Martínez Usarralde, Maria Jesús (Education Policy Analysis Archives, 2001)
This article analyzes how the patterns of cooperation among different institutions ensure quality professional preparation in terms of the production of an effective and regulated distribution of competencies. For this analysis we apply the comparative methodology of García Garrido to the Spanish and German models of professional development; and we review educational issues related to the administration, management, and supervision of the professional preparation system in the two countries both at the central and regional levels.